Analysis on the Significance of Effects from Operational Conditions on the Performances of Ultrasonic Atomization Dehumidifier with Liquid Desiccant. (2015) - Yang, Zili; Zhang, Kaisheng; Lian, Zhiwei
Abstract: In this work, simulations were carried out based on a L18×L8 cross-product orthogonal array to investigate the significance of the effects from inlet operational conditions on the performances of the ultrasonic atomization liquid desiccant dehumidification system (UADS), where dehumidification effectiveness was adopted as the performance indicator. Taguchi method was employed to analyze the results. It was found that though all of the inlet operational parameters revealed direct effects on the performances of UADS, the significance of their effects was quite different among which, the desiccant flow rate was the most sensible factor in improving DE while air humidity ratio exhibited the least significance. The results presented in this work may help in achieving the optimal running of the liquid desiccant dehumidification system.